Pemanfaatan Kapur Dolomit [Camg(Co3)2] Untuk Meningkatkan Ph Air Rawa Lebak Pada Pemeliharaan Benih Ikan Patin Siam (Pangasius Hypophthalmus) - Kurniasih Kurniasih; Dade Jubaedah; Mochamad Syaifudin (Universitas Sriwijaya, 2019)
Inland swamp water has low pH value 3-4, there fore is not suitable for striped catfish culture. Liming is one of the efforts to increase the pH of water. This research aims to increase the swamp water pH for survival rate and grow of catfish. This research used a completely randomized design four treatments and three replications with doses of 0,6 kg.m-2 equvalent to CaCO3 (P1), 0,9 kg.m-2 equvalent to CaCO3 (P2), 1,2 kg.m-2 equvalent to CaCO3 (P3) and 1,5 kg.m-2 equvalent to CaCO3 (P4). The parameters are water quality (temperature, pH, DO, ammonia, alkalinity, and hardness), growth and survival rate of striped catfish. The result showed that (P2) was the best treatment for increasing swamp water pH from 3,6 to 7,57 and soil pH from 3,5 to 7,60, survival rate 86,7%, absolute growth length 4,35 and absolute growth weight 8,30 g and feed efficiency 73,53%.